Bulbine natalensis (currently Bulbine latifolia) and select bulbine knipholones modulate the activity of AhR, CYP1A2, CYP2B6, and P-gp - Husain, Islam; Dale, Olivia R.; Manda, Vamshi; Ali, Zulfiqar; Gurley, Bill J.; Chittiboyina, Amar G.; Khan, Ikhlas A.; Khan, Shabana I. (Planta Medica, 2021)
Bulbine natalensis, an emerging medicinal herb on the global market with androgenic properties, is often formulated in dietary supplements that promote perceived sexual enhancement. However, to date, comprehensive safety studies of B. natalensis are lacking, particularly those related to its herb-drug interaction potential. The purpose of this study was to assess the inductive and inhibitory effects of extracts and pure compounds of B. natalensis on human cytochrome P-450 isozymes in vitro. Our findings demonstrated that both water and methanolic extracts of B. natalensis as well as knipholone, bulbine-knipholone, and 6′-O-methylknipholone dose-dependently increased mRNA expression encoded by CYP2B6, CYP1A2, and ABCB1 genes. Functional analyses showed that water (60 to 2.20 µg/mL) and methanolic (30 to 3.75 µg/mL) extracts and knipholones (10 to 0.33 µM) increased CYP2B6 and CYP1A2 activity in a dose-dependent manner. Additionally, water extract (60 µg/mL), methanolic extract (30 µg/mL), and knipholone (10 µM) caused activation of the aryl hydrocarbon receptor up to 11.1 ± 0.7, 8.9 ± 0.6, and 7.1 ± 2.0-fold, respectively. Furthermore, inhibition studies revealed that methanolic extract attenuated the activity of metabolically active CYP1A2 (IC50, 22.6 ± 0.4 µg/mL) and CYP2B6 (IC50, 34.2 ± 6.6 µg/mL) proteins, whereas water extracts had no inhibitory effect on either isoform. These findings suggest that chronic consumption of B. natalensis may affect normal homeostasis of select CYPs with subsequent risks for HDIs when concomitantly ingested with conventional medications that are substrates of CYP2B6 and CYP1A2. However, more in-depth translational studies are required to validate our current findings and their clinical relevance.
Keywords: Bulbine natalensis; aryl hydrocarbon receptor; cytochrome P-450s; herb-drug interactions; anthraquinones; mRNA expression; CYP inhibition; Xanthorrhoeaceae